Lambda nordica : populär tidskrift om homosexualitet. (Saltsjö-Boo : Institutet för sociala studier, 1989)
Fonds Suzan Daniel (FSD)
Periodiciteit : driemaandelijks
Redactie : Hasseluddsvägen 194, 132 37 Saltsjö-Boo, Zweden
Zweeds
Periodiek